2007
DOI: 10.1021/ic7005056
|View full text |Cite
|
Sign up to set email alerts
|

Seven-Coordinate Iron Complex as a Ditopic Receptor for Lithium Salts:  Study of Host−Guest Interactions and Substitution Behavior

Abstract: Interactions between the seven-coordinate tweezerlike [Fe(dapsox)(H2O)2]ClO4 complex (H2dapsox = 2,6-diacetylpyridine-bis(semioxamazide)) with different lithium salts (LiOTf, LiClO4, LiBF4, and LiPF6) in CH3CN have been investigated by electrochemical, spectrophotometric, 7Li and 19F NMR, kinetic, and DFT methods. It has been demonstrated that this complex acts as ditopic receptor, showing spectral and electrochemical ion-pair-sensing capability for different lithium salts. In general, the apparent binding con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 47 publications
(53 reference statements)
1
8
0
Order By: Relevance
“…Similar behavior has been reported for the binding of thiocyanate to another type of iron center. 32 The 720 nm band for the above-mentioned transient species is characteristic of a mixed-valent cyanobridged complex (a Prussian blue type compound) that could be independently o b t a i n e d e i t h e r f r o m t h e r e a c t i o n o f a q u a [Fe II (CN) 5−x (SCN) x (H 2 O)] 3− complexes in the presence of oxygen or upon addition of the corresponding Fe(III) complexes. 30 The UV/vis band at approximately 440 nm can be attributed to transient [(CN) 5 Fe(HNO)] 3− (inset in Figure 4A).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Similar behavior has been reported for the binding of thiocyanate to another type of iron center. 32 The 720 nm band for the above-mentioned transient species is characteristic of a mixed-valent cyanobridged complex (a Prussian blue type compound) that could be independently o b t a i n e d e i t h e r f r o m t h e r e a c t i o n o f a q u a [Fe II (CN) 5−x (SCN) x (H 2 O)] 3− complexes in the presence of oxygen or upon addition of the corresponding Fe(III) complexes. 30 The UV/vis band at approximately 440 nm can be attributed to transient [(CN) 5 Fe(HNO)] 3− (inset in Figure 4A).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…22,23,25,60 Because these complexes represent mimics of superoxide dismutase (SOD) and ditopic receptors for lithium salts, they are of the utmost importance, and hence detailed kinetic and mechanistic experimental studies were reported previously. 29 2 ] n+ , explaining the nature of correctly tuned redox potentials in catalytic superoxide disproportionation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Although ionophores have been considered early on, the synthetic ionophores with high affinity and selectivity for lithium ion is a challenging task. In this regard, considerable efforts have been given on crown ether derivatives, spherands, hemispherands, , metallamacrocycles, and various lithium ionophores/​receptors which often require substantial synthetic efforts.…”
Section: Introductionmentioning
confidence: 99%